Information Literacy Education among Faculty and Students: The Role of Laz Otti Memorial Library, Babcock University, Nigeria - (:unkn) unknown (My University, 2015)
The digital divide between the developed and developing world has widened due to lack of information literacy skills in developing countries. Library users within an academic environment have limited skills in the area of information literacy, as it is not discussed extensively in their academic course curriculum which has prompted library users with the challenges of searching, locating, identifying, recognizing, evaluating, using and applying the knowledge gained from the array of information resources; synthesizing new and old information to improve research output and productivity. This paper intends to identify the various strategies deployed by Laz Otti Memorial Library to investigate the various Information Literacy Education programmes deployed by Laz Otti Memorial Library, determine the role of Laz Otti Library Memorial in Information Literacy Education Programme and find out the various information Resources available in Laz Otti Memorial Library.The findings of this study will serve as a Blueprints to boast Library managers/university administrators that information literacy education is a fundamental right for both students and staff and will bridge the digital divide between the library clientele and the information through Information Literacy Education.
Keywords: African Research